PENGARUH INDUSTRI PENGOLAHAN, TENAGA KERJA, DAN INFLASI TERHADAP PERTUMBUHAN EKONOMI DI JAWA TIMUR TAHUN 1981-2018 - Maya Wulan Kusumawardani; Ida Nuraini (Jurnal Ilmu Ekonomi JIE, 2020)
Economic growth is one indicator that is used as a benchmark for the success of the development of an area in East Java whether it has increased or decreased. This study aims to determine how much influence or variables that can influence economic growth in East Java. The analytical tool used in this study is multiple linear regression with time series data interpolated with statistical measurements using Eviews computer by using the classic assumption test and the F t-test analysis. In the results of research that have been carried out it is known that the processing industry has a positive and significant influence on economic growth in East Java with the results of the coefficient 24.73977 and the probability result of 0.0117 as the labor variable which also has a positive and significant effect with the results obtained the regression coefficient is 45.17394 and the probability result is 0.0229 while the inflation variable has a negative and significant effect on economic growth with the results of the regression coefficient of -0.251741 with a probability  result of 0.0043.